Review on hybrid geothermal and solar power systems. (20th March 2020) - Li, Kewen; Liu, Changwei; Jiang, Shanshan; Chen, Youguang
Abstract: Despite having many promising advantages for environment and sustainability, renewable energy is not yet cost-competitive with crude oil in all locations due to issues with low capacity factor, grid instability, and intermittency. In particular, hybrids of geothermal and solar power systems (e.g. photovoltaic and concentrated solar power) have been shown to be mutually beneficial and a promising combination of renewable energy sources. Worldwide, there are many areas with both high geothermal heat flux and surface radiation, which makes integration of geothermal and solar energies possible. The geothermal industry targets geothermal resources with high temperatures, because the efficiency of power generation from thermal energy is directly proportional to the resource temperature. Unfortunately, most of the geothermal resources have low to moderate temperatures of about 150 °C or less. Alternatively, solar could be used to increase the temperature of geothermal fluids, significantly improving the efficiency of geothermal power generation. Geothermal fluids can serve as storage systems for solar energy, which may solve many problems of solar systems such as weather dependence and instability. On the other hand, the inclusion of photovoltaic (PV) panels in a geothermal power plant may be able to cope with the peak power demand during day time, which is helpful to extend the lifespan of geothermal fields. In this review, we briefly discuss the fundamentals of solar and geothermal power systems. Secondly, we review important progress in the literature towards stand-alone solar or geothermal power systems. Thirdly, we highlight the configurations, mechanisms, and unique features of hybrid solar-geothermal power plants, while also developing a methodology to evaluate their efficacy. Finally, we assess and classify the predominant hybrid solar-geothermal power systems by summarizing and analyzing the stand-alone efficiency, hybrid efficiency, and the percentage of incremental efficiency from the literature. It can be concluded that combining geothermal and solar systems will increase the efficiency and power generation of both energy systems, representing an exciting opportunity for both scientific and practical exploration.